KAJIAN INTEGRATIF SITUS PRASEJARAH Dl KAWASAN MANGKULIRANG, KUTAI TIMUR (Integrative Study of Prehistoric Site In Mangkulirang Region, East Kutai) - nFN Nasruddin (BALAI ARKEOLOGI PAPUA, 2016)
Studies on karst is a study that can be done hotisticaliy, because in the karst region them are various potentials such as; prehistoric archaeological remains which are quite old, there am groups of people who have local knowledge seekers swallow nest, traditional agricultural activities and the utilization of the site of the settlement (settlement area), as well as habits embodied in traditions and art. Through archaeological approach to spatial spatial archeology), the archaeological research in East Kutai Karst, not only reveal the spatial and temporal aspects alone, but as a whole want to explain culturally and physically; synchronic and diachronic this region inhabited by humans. Mangkulirang karst area is so vast traffic would require a study to obtain an explanation; subsistence, technology and the ancient environment, as well as the adaptation of the system that have become extinct Cave sites and niches in the Mangkulirang a valuable contribution to the knowledge of the history and prehistory of cultural processes. Any kind of potential above require management in the context of synergy, participation and shared responsibility with the local authorities, cross-institutional and community organizations, as well as cross-sectoral and multi-disciplinary to minimize conflicts of the various interests in the karst region in the management and preservation of cultural heritage Indonesia. AbstrakKajian tentang karat adalah kajian yang dapat dilakukan secara holistik, karena di daiam kawasan karst tendapat berbagai potensi seperti; tinggalan arkeologis prasejarah yang cukup tua, terdapat keiompok-kelompok masyarakat yang memiliki kearifan lokal, para pencari sarang waist, aktivitas pertanian tradisional dan pemanfaatan menjadi lokasl pemukiman, serta kebiasaan-kebiasaan yang dlwujudkan daiam bentuk tnadisl dan kesenian. Melalui pendekatan arkeologi kemangan, maka penelitian arkeologi di Karst Kutai Timur, tidak hanya mengungkapkan aspek spasial dan temporal saja, tetapl secara utuh ingin menjelaskan secara kultural maupun fisikal; sinkronik maupun diakronik kawasan ini dihunl manusia. Kawasan karst Mangkulirang yang begitu luas tentunya memerlukan iintas kajian untuk memperoleh penjelasan; subsistensi, teknologi dan lingkungan purba, serta sistem adaptasi yang teiah punah. Situs gua dan cernk di kawasan Mangkulirang dapat memberlkan kontribusl berharga tarhadap pengetahuan sejarah dan proses budaya prasejarahnya. Sagaia jenis potensi di atas memerlukan pengeioiaan daiam rangka sinergitas, peran serta dan tanggung jawab bersama dengan pemerintah daerah, iintas kelembagaan dan organisasi masyarakat, maupun lintas sektoral dan multi disiplin untuk meminimalisir benturan atas berbagai kepentingan di kawasan karst dalam rangka pengelolaan dan pelestarian cagar budaya Indonesia.",